En búsqueda del equilibrio entre la protección de datos personales, el deber de transparencia y el derecho de acceso a la información pública - Rivera Prado, Mariafernanda (2022)
Each country that has developed a set of personal data protection rights and access to public information has done so by addressing specific needs, according to its own socio-historical cultural context; and Peru is no exception. To fully understand the protection of these rights and determine the criteria with which a sufficient balance between them is guaranteed, we necessarily have to go back in time and observe the reason why they emerged in Europe, the United States of America and Latin America. Understanding the origin of these rights from their historical context will allow us to determine if the Peruvian legislator has implemented the norm on the protection of personal data in coherence with their reality and needs; and if the authorities in Peru correctly settle the cases in which the rights contained in the Law of Transparency and Access to Public Information and the right to the protection of personal data conflict. Based on a thorough analysis of the above, this investigation will propose the criteria that the competent authority must apply to deliberate on the aforementioned controversy and thus seek a reasonable balance in the protection or limitation of these rights.